Investigation Of Aerobic Degradation Of Industrial Wastewater Containing High Organic Matter: Kinetic Study - M. Sarioglu Cebeci; I. Senturk; U. Guvenin (European Scientific Journal, ESJ, 2016)
Aerobic biodegradability of the industrial wastewater (IW) containing high level of COD was assessed in laboratory-scale batch reactors. Two experimental runs were carried out at a ratio of substrate-tomicroorganisms concentration So/Xo equal to 0,5 and 3,5 g COD /g MLVSS while equal to 1 ratio of synthetic wastewater to IW. Chemical oxygen demand, pH, and alkalinity were determined during the experiments. An increase in the influent substrate concentration not caused a decrease in COD removals at similar times of working. Since the inoculum was previously acclimatized to COD concentration, a substrate (mixture of the synthetic and industrial wastewater) inhibition at the higher concentrations of COD most probably was absent. It was found that a first-order kinetics adequately described the variation of COD removal with time. The values of the firstorder reaction constants were found to be 0,3083 and 0,2038 d-1 for Runs 1– 2, respectively.